Bioinspired Composites: Hierarchical and Heterogeneous Bioinspired Composites—Merging Molecular Self‐Assembly with Additive Manufacturing (Small 28/2017). Issue 28 (20th July 2017) - Rajasekharan, Anand K.; Bordes, Romain; Sandström, Carl; Ekh, Magnus; Andersson, Martin
Abstract : In article number1700550, Martin Andersson and co‐workers, report a new method to form multiscale, bioinspired composite materials by combining bottom‐up molecular self‐assembly and top‐down additive manufacturing. The composites are ordered constructs with an organic‐inorganic interpenetrating nanostructure aligned over centimeter length‐scales, with structural features as small as 10 nm. The composites display a hierarchical structure, composition and crack‐resist mechanics on similar length scales as biological materials like bone and the bone‐cartilage composite.